Upaya Perlindungan Hukum Terhadap Perempuan dan Anak Korban Kekerasan Seksual di Provinsi Bali: Legal Protection Efforts Against Women and Children Victims of Sexual Violence in Bali Province - Yuliartini, Ni Putu Rai; Mangku, Gede Dewa Sudika; Putri, Putu Pipit Pricellia Eka (Fakultas Hukum Universitas Negeri Semarang, 2021)
Sexual violence against women and children is a form of action that violates human rights. As it is known, the human rights of women and children have been guaranteed and regulated in the 1945 Constitution of the Republic of Indonesia and the Law on Human Rights. Therefore, protection of the rights of women and children from violence should be respected, upheld and enhanced human dignity without discrimination, welfare and justice for women and children. Violence is any act against the law with or without using physical and psychological means that causes danger to one's life, body or causes the deprivation of one's freedom. The purpose of this paper is to provide legal protection to women and children who are victims of sexual violence in Bali Province. By using juridical-normative research methods based on primary, secondary, and tertiary legal materials such as laws and regulations, court decisions, legal theory, and can be in the form of opinions of scholars related to existing problems. Analyzed qualitatively with descriptive-prescriptive presentation. There it was later found that until now, especially in Bali, the existence of women and children victims of sexual violence has not received adequate services so that legal protection efforts are needed for victims of sexual violence in Bali Province. Thus, the law exists to provide protection for women and children who are victims of sexual violence.